Creepy crawly crime - Reynolds, Aaron, 1970- (Joey Fly private eye, 2012)
"Have you ever had one of those moments? You know--when you're trying to find a stolen diamond pencil box for your beautiful butterfly customer, your mosquito witness won't give you any information, and your clumsy scorpion assistant has just tampered with your only bit of evidence? Joey Fly has those moments a lot. In fact, he's probably having one right now. But never fear. When Joey Fly, private eye, is on the case, nothing can stop him from getting his bug!"--Page 4 of cover.